تمثلات فئة مشرفي التربية حول مسارهم المهني و فرص الترقية - قودة, عبد الهادي (كلية العلوم الاجتماعية, 2025)
أظهرت نتائج البحث تبايناً في تصورات مشرفي التربية حول مسارهم الوظيفي، حيث تفاوتت بين تمثلات سلبية تعكس شعورهم بالتهميش وغياب وضوح الآفاق، وأخرى إيجابية تظهر ثقتهم في مؤهلاتهم وتطلعاتهم لمستقبل أفضل. في الفصل الأول، تم استعراض الإطار القانوني لمهنة مشرف التربية، مع تحليل المسار التاريخي للتطورات القانونية والتصنيف والترقية. أما الفصل الثاني فركز على العلاقة بين الطموح المهني والتكوين، حيث تبين أن هذه العلاقة تتأثر بعوامل متعددة قد تكون محفزة أو محبطة. كما تم التركيز على أهمية التكوين والتأهيل في تعزيز فرص الترقية وتحقيق الطموحات المهنية لمشرفي التربية. The research results revealed a divergence in educational supervisors' perceptions of their career paths. These perceptions ranged from negative representations reflecting feelings of marginalization and lack of clear prospects, to positive ones demonstrating confidence in their qualifications and aspirations for a better future. Chapter one reviewed the legal framework governing the profession of educational supervisors, analyzing the historical evolution of legal developments, classification, and promotion. Chapter two focused on the relationship between professional ambition and training, showing that this relationship is influenced by various personal, social, and organizational factors, which can either motivate or discourage. The chapter also emphasized the importance of training and qualification in enhancing promotion opportunities and achieving professional goals for educational supervisors.
دراسة على عينة من المشرفين بالمؤسسات التربوية لبلدية سيرات
Keywords: مشرف التربية- المسار المهني- فرص الترقية